Target Language Use in EFL Classrooms: Turkish EFL Teachers’ Beliefs and Practices - Korkmaz, ?ule Çelik (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2021)
Considering the teacher talk as the main input in English as a foreign language (EFL) classrooms, this descriptive study aimed to elucidate the beliefs and practices of Turkish EFL teachers regarding their use of a foreign language, namely English (L2) in their classrooms by taking into account school types, experience, and travelling abroad as variables. Accordingly, 308 EFL teachers from different regions of Turkey were given a questionnaire with two parts, firstly beliefs and then practices, to clarify this prominent issue. The results indicated the high level of teacher awareness about the necessity for using L2 for several reasons but without dismissing the use of their native language, namely Turkish (L1). Conversely, the study highlighted the clashes between their espoused beliefs and practices. Furthermore, being more experienced teachers and working in primary or high schools were not reported as significant factors in teacher agency in making language choices to teach L2 whereas working in state or private schools and visiting English speaking countries revealed significant differences in the beliefs and practices of the teachers with regard to their use of L2 to teach L2. The results were discussed with suggestions to maximize L2 use in EFL classrooms.